Anoxia induces time-independent K+ current through KATP channels in isolated heart cells of the guinea-pig. - Benndorf, K (1992)
1. Isolated ventricular heart cells of the guinea-pig were exposed to anoxia (PO2 < 0.1 Torr) which induced a time-independent K+ current. This current was studied with the patch clamp technique in the whole-cell and cell-attached configuration. 2. The latency until anoxia-induced changes of whole-cell current developed was distributed exponentially (mean 10.5 min; n = 41). The current was abolished within 2-4 s of reoxygenation. 3. The reversal potential of the anoxia-induced change of whole-cell current at 5.4 and 15 mM [K+]o was -82 and -61 mV, respectively. 4. Analysis of current noise in whole-cell current during the phase of the slow development of the anoxia-induced current yielded a slope conductance of unitary currents of 8.1 pS (5.4 mM [K+]o) which is far below the 30 pS of KATP channels in inside-out patches with no Na+ and Mg2+ in the bath. 5. Reduced unitary current induced by anoxia was recorded in single-channel measurements with 10.4 mM-K+ in the pipette. 6. Using 150 mM-K+ in the pipette, anoxia caused unitary inward currents with a slope conductance of 83 pS. The open probability of the channels (P(o)) reached maximum values between 0.6 and 0.95. The channels closed within 1-3 s of reoxygenation. 7. At voltages between -85 and -45 mV and maximum P(o), open time histograms were dominated by a fast exponential (tau 01 = 0.55 +/- 0.21 ms, mean +/- S.D.) and one or two slow exponentials. 8. Voltage ramp experiments showed that single-channel currents were slightly rectifying in the inward direction. 9. Glibenclamide (1 microM) reversibly blocked the anoxia-induced whole-cell and single-channel currents. 10. It is concluded that during anoxia it is only KATP channels which open by a sufficient decrease of submembrane ATP levels.